A Case of Early Stage Bladder Carcinosarcoma in Late Recurrence of Urothelial Carcinoma after Transurethral Resection - Daisaku Hirano; Toshiyuki Yoshida; Daigo Funakoshi; Fuminori Sakurai; Shou Ohno; Yoshiaki Kusumi (Case Reports in Urology)
Carcinosarcomas of the urinary bladder are rare biphasic neoplasms, consisting of both malignant epithelial and malignant mesenchymal components, and the prognosis of this tumor is unfavorable in most patients with even possibility of resection of disease. A 77-year-old male with a history of transurethral resection (TUR) of urothelial carcinoma (UC) of the bladder and adjuvant intravesical chemotherapy with pirarubicin 10 years ago revisited our department with a gross hematuria. Cystoscopy demonstrated an approximately 2.5 cm nonpapillary tumor on the right wall of the bladder. Pelvic MRI showed the tumor without extending the base of the bladder wall. The tumor could be completely removed with TUR. The malignant epithelial elements consisted of high-grade UC and the majority of mesenchymal components were fibrosarcomatous differentiation based on immunohistochemical studies. The tumor could be pathologically also suspected to be an early stage on TUR specimens. Although he has received no additional intervention due to the occurrence of myocardial infarction at three weeks after the TUR, he has been alive with no evidence of recurrence of the disease 27 months after the TUR. Some early stages of bladder carcinosarcoma might have a favorable prognosis without aggressive treatments.